Canonical correlation analysis for the determination of relationships between plant characters and yield components in red pepper (Capsicum annuum L. var. conoides (Mill.) Irish) genotypes - Cankaya, S.; Balkaya, A.; Karaagac, O. (Spanish Journal of Agricultural Research, 2010)
In this study, a canonical correlation analysis (CCA) was used to estimate relationships between plant characters (X set-fruit length (FL), fruit width (FW), fruit wall thickness (FWT), placenta length, stem thickness, plant height (PH), leaf length, leaf width, flowering time (50%), and time to maturity), and yield components (Y set-total fruit weight per plant (FW/P), average fruit weight and number of fruits per plant (FN/P)) of 56 red peppers (Capsicum annuum L. var. conoides (Mill.) Irish) in populations collected from the Samsun province in the Black Sea Region of Turkey. All canonical correlation coefficients (0.708, 0.635, 0.413) between the pairs of canonical variables were found to be significant (P < 0.01). The findings obtained from the CCA indicate that FN/P had the largest contribution for the explanatory capacity of canonical variables estimated from yield components of 56 red pepper populations when compared with other yield components. FL and PH had largest contribution for the explanatory capacity of canonical variables estimated from plant characters when compared with other characters. The results of this study show that PH, FWT and FW should be used with the aim of increasing yield per plant in red pepper genotypes.